Familial risk for endometriosis and its interaction with smoking, age at menarche and body mass index: a population‐based cohort study among siblings. (14th June 2021) - Kim, HJ; Lee, H‐S; Kazmi, SZ; Hann, HJ; Kang, T; Cha, J; Choi, S; Swan, H; Kim, H; Lee, YS; Ahn, HS
Abstract : Objective: To quantify familial risk of endometriosis among full siblings and examine interactions between family history and smoking, age at menarche or body mass index (BMI). Design, setting and population: Population‐based nationwide cohort study. Methods: Using data from the Korean National Health Insurance and Screening Programme databases on kinship, healthcare utilisation, lifestyle and anthropometrics, we identified 2 109 288 women with full siblings and their environmental risk factors from 2002 to 2018. Familial risks were estimated using Cox proportional‐hazards models, represented as incidence risk ratios (IRR) with 95% CI. Interaction between family history and smoking, age at menarche or BMI were assessed on an additive scale. Main outcome measures: IRR of endometriosis among women with and without affected siblings. Results: From 19 195 women with affected siblings, 1126 developed endometriosis with an incidence of 35.45/10 000 person‐years. Familial risk of endometriosis with versus without affected siblings was increased to IRR 2.75 (95% CI 2.25–3.36), and the highest risk was with affected twins (IRR 6.98; 95% CI 4.19–11.62). Women with both a family history and either smoking, early menarche or low BMI had a significantly higher risk of endometriosis compared with the general population and can be regarded as a high‐risk group, the IRRs were 4.28 (95% CI 2.43–7.55), 3.47 (95% CI 2.82–4.26) and 3.09 (95% CI 2.68–3.56), respectively. Substantial effect modification of the associations was noted by smoking and early menarche, as their combined risk with family history exceeded the sum of their individual risks, which was also statistically significant. Conclusion: Genetic factors are the primary contributor to the familial aggregation of endometriosis. Significant gene–environment interaction exists between family history and smoking or early menarche. Tweetable abstract: Significant gene–environment interaction exists between family history of endometriosis and smoking or early menarche. Tweetable abstract: Significant gene–environment interaction exists between family history of endometriosis and smoking or early menarche.